2004
DOI: 10.1007/s11130-004-0029-y
|View full text |Cite
|
Sign up to set email alerts
|

Fatty Acid Composition of Serum, Adipose Tissue, and Liver in Rats Fed Diets Containing Corn Oil or Cottonseed Oil

Abstract: There have been few studies on the effect of cottonseed oil (CSO), one of the most commonly used vegetable oils in the United States, on indices of lipid status either in the rat or in any other species. Previous studies with rats have focused on the effect of CSO, versus that of other vegetable oils, on the concentration of cholesterol in serum and liver or on a limited number of fatty acids in serum, adipose tissue, or liver. The present study was designed to compare more fully than in previous studies the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Stearic acid accounts for 3% of the total fatty acid content, palmitic acid 22%, and linoleic acid 54% [9]. Another study by Radcliffe and Narins showed that rats fed CSO had increased adipose tissue levels of saturated fatty acids [10]. Given that saturated fats are well known to be associated with atherogenic lipid profiles, these separate findings are somewhat puzzling.…”
Section: Introductionmentioning
confidence: 99%
“…Stearic acid accounts for 3% of the total fatty acid content, palmitic acid 22%, and linoleic acid 54% [9]. Another study by Radcliffe and Narins showed that rats fed CSO had increased adipose tissue levels of saturated fatty acids [10]. Given that saturated fats are well known to be associated with atherogenic lipid profiles, these separate findings are somewhat puzzling.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the cattle fed CSO for 70 to 80 days has more C18:0 SFA and less C16:1 and C18:1 UFAs in adipose tissue (Yang, Larsen, Smith, & Tume, 1999). Radcliffe et al (2004) found that the levels of SFAs in adipose tissue of mice were much higher for the CSO group than the control, together with lower levels of monounsaturated fatty acids (MUFAs) and n-3 PUFAs. Evans et al also observed that eggs, blood plasma, and tissues from hens fed a diet that contained crude cottonseed oil contained a higher proportion of stearic acid and a lower proportion of oleic acid than that from hens fed the normal diet (Evans, Bandemer, Anderson, & Davidson, 1962;Evans, Davidson, & Bandemer, 1961;Evans, Flegal, Foerder, Bauer, & La Vigne, 1977).…”
Section: Introductionmentioning
confidence: 95%
“…Radcliffe et al. () found that the levels of SFAs in adipose tissue of mice were much higher for the CSO group than the control, together with lower levels of monounsaturated fatty acids (MUFAs) and n‐3 PUFAs. Evans et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cotton seed oil known in Cameroon under the brand name Diamaor is one of the best polyunsaturated oil available in the market. The major fatty acids found in its composition are linoleic acid (52.89%) oleic acid (16.35%) and palmitic acid (25.39%) [13]. It is used in household for cooking, frying and seasoning.…”
Section: Introductionmentioning
confidence: 99%